EXPLORING THE CHALLENGES OF CONVENTIONAL BANKING PRACTICES AND PROSPECTS OF INTRODUCING AN ISLAMIC BANKING IN TAJIKISTAN: USING QUALITATIVE APROACH - Sharofiddin, Ashurov; Idris, Ahmed Fauzi Bin; Othman, Anwar Hasan Abdullah (Universitas Muhammadiyah Yogyakarta, 2018)
The purpose of this research is to explore the challenges of current banking practices in Tajikistan and investigate the prospects of introducing the new Islamic banking system. In which the Islamic banking may help in bring back the trust to the people for dealing with the banking system that will lead to enhance the economy growth. This study applied the qualitative method by conducting in depth interviews with the experts comprising seven respondents. The result of respondents showed that there is list of challenges that current banking practices facing in Tajikistan. This therefore encourage for introducing an Islamic banking system in Tajikistan. Among the challenges in Conventional Banking system that respondents identified are distrust, an interest-based (Ribâ) system, and long processes with complicated systems. This is because the listed challenges by respondents are crippling the entire banking system, if the authority is not concerning for catering the existed challenges. Moreover, the findings signify the challenges of conventional banking practice that the authorities of the country and practitioners must avoid when Islamic banks are established. In addition, the practitioners need to focus on improving the current banking practice to avoid the challenges identified in the study.